Isomers of 4-[18F]fluoro-proline: Radiosynthesis, Biological Evaluation and Results in Humans Using PET - Geisler, Stefanie; Ermert, Johannes; Stoffels, Gabriele; Willuweit, Antje; Galldiks, Norbert; P. Filss, Christian; J. Shah, Nadim; H. Coenen, Heinz; Langen, Karl-Josef (Current Radiopharmaceuticals, 2014)
Proline and hydroxyproline represent major constituents of mammalian structural proteins, especially of collagen. An efficient radiosynthesis of the 18F-labeled proline derivatives cis-/trans-4-[18F]fluoro-L-proline was developed two decades ago with the aim to investigate various diseases with altered collagen synthesis using Positron-Emission- Tomography (PET). A number of studies have explored cis-4-[18F]fluoro-L-proline uptake in various pathologies associated with increased collagen formation and in neoplastic lesions, but so far the results have not been very promising. Trans-4-[18F]fluoro-L-proline has not yet been investigated in detail, however the compound exhibits considerable differences in metabolic behavior and biodistribution compared with its cis-enantiomer. In recent years, the D-isomers of cis- /trans-4-[18F]fluoro-proline have been considered as PET tracers as well, and it was observed that both exhibit a preferred uptake into the brain compared with their L-isomers. Surprisingly, a high uptake of cis-4-[18F]fluoro-D-proline was found in brain areas exhibiting secondary neurodegeneration as well as in areas of radionecrosis after treatment of brain tumors. In this article, the present knowledge on the biological and physiological properties of cis-/trans-4-[18F]fluoro-D/L-proline and the results in various pathologies are reviewed, including some previously unpublished results from our laboratory.
Keywords: neurodegeneration